PENGARUH KOMPETENSI PEDAGOGIK, KOMPETENSI PROFESIONAL DAN KOMITMEN TERHADAP KINERJA GURU (DI SDI SALAFIYAH GONDANGLEGI MALANG) - Rudi Setiawan; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This research aims to know the influence of Pedagogic Competence, Professional Competence and commitment to the performance of the teacher in the Sdi Salafiyah Gondanglegi Malang. The type of research used is Experimental . The data used are the primary data and secondary data, obtained from the now, that is by collecting data from master Sdi Salafiyah Gondanglegi Malang.Population and Sample which became the object of this research is the whole teacher Sdi Salafiyah Gondanglegi Malang, i.e. as many as 32 teachers. Technique of data analysis in this study uses the test validity, reliability test, test, test the normality assumption of classical, linear multiple regression test and test hypotheses.The results of the analysis of the data shows that: (1) the competence of Pedagogic effect significantly to Teacher Performance Sdi Salafiyah Gondanglegi Malang, (2) the professional competence of the influential Teacher Performance significantly to Sdi Salafiyah Gondanglegi, Malang While (3) commitment to a significant effect on performance Guru Sdi Salafiyah Gondanglegi MalangKeywords: Pedagogic Competencies, Professional Competence, Commitment and Performance of the Teacher